On the reliability of renewed system with dependent elements - Sapagovas, J. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:И. Сапаговас. О надежности восстанавливаемой системы с зависимыми элементамиJ. Sapagovas. Atstatymo sistemos su priklausomais elementais patikimumo klausimu